Analisis Campur Kode Dalam Acara Podcast Deddy Corbuzier Dengan Fiki Naki Oh Fiki Naki - Florentina Br Manurung; Lastri Marito Marbun; Jessika Caroline Harahap; Serina Angela Sitompul; Jernih Martha Banjar Nahor; Lidya Elizabeth Sihaloho; Eka Putri Saptari Wulan (Jurnal Mahasiswa Kreatif, 2024)
Code mixing is a habit and role speech factor that is brought out in the use of language. There are various forms of code mixing in the interactions that occur between the narrator and the source in the podcast program. Deddy Corbuzier's program was the object, with that the research title "Analysis of Code Mixing in Deddy Corbuzier's Podcast Show with Fiki Naki" was raised. The method used in this research is a qualitative descriptive method. Forms of code mixing were found in speech carried out on Deddy Corbuzier's Podcast with Fiki Naki, namely full words, phrases and repetition of words. Two types of code mixing were found in Deddy Corbuzier's podcast story with Fiki Naki, namely inward code mixing and outgoing code mixing.